Dehumanisasi Bangsa Palestina - Al Farauqi, Mohamad Dziqie Aulia; Alisa, Azizah Nurfadillah (Indonesia Center for Middle East Studies, 2025)
The Israeli-Palestinian conflict, especially after October 7, 2023, has attracted significant attention from the international community. Although global sympathy for Palestinian victims is increasing, online spaces are also witnessing a rapid increase in hate speech by Israelis against Palestinians. This research aims to analyze how the Israeli government employs tactics of governmentality to produce and sustain social control, drawing on Michel Foucault’s theoretical framework. Furthermore, this study examines the government's indoctrination efforts against Israelis, which culminates in the construction of a narrative of dehumanization and the cultivation of hatred against Palestinians. This study used a descriptive qualitative method and used a literature review for data collection. The findings show that the indoctrination carried out by Israel, built through the discourse of dehumanization of Palestine (the regime of truth), has succeeded in instilling hatred of Palestinians among Israelis. This indoctrination and discourse formation effort is carried out through a number of mechanisms, such as the conscription system, the instrument of nationalism, and the formation of a collective perception of Israel.